Successful administration of venovenous extracorporeal membrane oxygenation through the modified Blalock–Taussig operation in an infant with graft dysfunction after the Norwood procedure - Kanao-Kanda M; Kunisawa T; Yamamoto K; Kanda H; Iwasaki H (Dove Medical Press, 2015)
Megumi Kanao-Kanda, Takayuki Kunisawa, Kunihiko Yamamoto, Hirotsugu Kanda, Hiroshi Iwasaki Department of Anesthesiology and Critical Care Medicine, Asahikawa Medical University, Asahikawa, Hokkaido, JapanInsufficient pulmonary blood flow through a right ventricle-to-pulmonary artery conduit following the Norwood procedure is remediable by adding a modified Blalock–Taussig shunt (MBTS).1 First, however, perioperative hypoxemia must be managed. Venovenous extracorporeal membrane oxygenation (VV-ECMO) is likely to be a useful method for respiratory support in such cases.2,3 We present the case of a 2-month-old patient with graft dysfunction after the Norwood procedure who underwent MBTS with VV-ECMO support.